Pengaruh Model Produk Terhadap Tingkat Volume Penjualan : Studi Kasus Pada Telepon Selular Merek Nokia Pada PT. Bimasakti - Tobing, Maju Lumban (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2004)
Conducting analysis by means of simple linear correlation coefficient, where the number of atributes of Nokia celular telephone sold by PT. Bimasakti as variable of x, and the number of celular telephone units sold in one selling period namely a quarter for one Nokia celular telephone model as variable of y, result 0,8. The mentioned rate means that Nokia celular telephone model has close correlation with PT. Bimasaktiâs selling volume degree as 0,8 and the correlation positive. After enumerating by means of regression coefficient to find out the influence of Nokia celular telephone model to firmâs selling volume degree, resulted Y=-6,79+0,65x where rate of Y is assessment rate of Y. Keywords : Selling Volume; Model of Product.